2019
DOI: 10.18314/jdms.v2i1.1633
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Virtual Surgical Planning in Increasing the Predictability in Orthognathic Surgery

Abstract: Purpose: To evaluate our surgical outcomes by comparing our surgical plan to the outcome of the surgery and evaluate our efficacy using Virtual Surgical Planning and Medical Modeling software. Our aim is to determine the quality and validity of Virtual Surgical Planning when comparing pre-surgical plans with post-surgical outcomes. Patients and Methods: A cohort study was conducted for patients who underwent orthognathic surgery at a single institution.  Utilizing virtual plans and models, select points for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In addition, the accuracy of the surgical movements predicted were not significantly different for most landmarks, regardless of gender and type of deformity. In a small study, Quereshy et al [ 51 ] also concluded that VSP is useful for orthognathic surgery since it can yield favorable and accurate outcomes. Later, in a sample of over 60 patients, Kwon et al [ 52 ] investigated discrepancies between actual and planned movements in segmental maxillary osteotomies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the accuracy of the surgical movements predicted were not significantly different for most landmarks, regardless of gender and type of deformity. In a small study, Quereshy et al [ 51 ] also concluded that VSP is useful for orthognathic surgery since it can yield favorable and accurate outcomes. Later, in a sample of over 60 patients, Kwon et al [ 52 ] investigated discrepancies between actual and planned movements in segmental maxillary osteotomies.…”
Section: Discussionmentioning
confidence: 99%